Regional Geology and Tectonics : Principles of Geologic Analysis. - Roberts, D. G. (David G.) (Elsevier Science, 2012)
Expert petroleum geologists David Roberts and Albert Bally bring you Regional Geology and Tectonics: Principles of Geologic Analysis, volume one in a three-volume series covering Phanerozoic regional geology and tectonics. It has been written to provide you with a detailed overview of geologic rift systems, passive margins, and cratonic basins, it features the basic principles necessary to grasping the conceptual approaches to hydrocarbon exploration in a broad range of geological settings globally. A "how-to" regional geology primer that provides a detailed overview of tectonics, rift systems.